(untitled) (Nigerian Journal of Technology, 2016)
Construction projects are prone to conflicts. This is due to the multiplicity of individuals handling different phases of the projects. Empirical evidence from previous studies shows that conflicts affects projects outcomes, if not properly managed. Identification of the significant causes of conflicts is critical to minimizing the likelihood of conflicts occurring in projects. Thus, this study was aimed at identifying and assessing causes of conflicts in Nigeria based on the perception of consultants and contractors. To achieve the study’s objectives, a 64-item questionnaire was used to collect information on experiences of construction professionals on the causes of conflicts in Nigerian construction projects. Responses from 69 professionals working for consultants and contractors were analysed. Seven significant causes of conflicts in the Nigerian context were identified. Based on the survey results, poor financial projections on the client’s side was identified as the most significant cause of conflicts. Furthermore, it was found that there are no difference in the perception of both groups of respondents. Taken together, these findings support strong recommendations on the need for effective management of finance on the client side, and engagement of experienced consultants in project. Implementation of these recommendations will minimize the likelihood of conflicts occurring in construction projects. http://dx.doi.org/10.4314/njt.v35i2.6